Analysis of the individual and aggregate genetic contributions of previously identified serine peptidase inhibitor Kazal type 5 (SPINK5), kallikrein-related peptidase 7 (KLK7), and filaggrin (FLG) polymorphisms to eczema risk. - IRVINE, ALAN (My University, 2008)
BACKGROUND: Polymorphisms in the serine protease inhibitor gene serine peptidase inhibitor Kazal type 5 (SPINK5) and the serine protease kallikrein-related peptidase 7 gene (KLK7) appear to confer risk to eczema in some cohorts, but these findings have not been widely replicated. These genes encode proteins thought to be involved in the regulation of posttranslation processing of filaggrin (FLG), the strongest identified genetic risk factor for eczema to date. OBJECTIVES: We sought to clarify the individual risk of eczema conferred by the SPINK5 polymorphism rs2303067 (Glu420Lys) and a previously described insertion in the 3' untranslated region of KLK7 and to examine potential epistatic effects between these variants and FLG mutations. METHODS: Initially, we examined the effects of these polymorphisms and FLG in 486 unrelated patients from a German family-based study, an additional 287 German patients, and 418 unrelated Irish/English patients with eczema (n for 3 genes studied = 1191 vs 4544 control subjects). We then additionally studied the SPINK5 polymorphism and FLG mutations in 1583 patients with eczema from the Avon Longitudinal Study of Parents and Children cohort (sample size for 2 genes studied = 2774 vs 10,607 control subjects). RESULTS: No association was seen with the SPINK5 or KLK7 variants in the case-control analysis; however, a weaker effect was observed for the SPINK5 variant with maternal transmission in the family-based study. No interactions were seen between the polymorphisms in KLK7, SPINK5, and FLG. CONCLUSION: The SPINK5 420LysSer mutation confers a risk of eczema when maternally inherited but is not a major eczema risk factor. The KLK7 insertion appears to confer no risk of eczema. We found no interaction between the SPINK5 risk allele or the putative KLK7 risk allele and FLG mutations.
Keywords: SPINK5 420LysSer mutation; Immunology, Inflammation & Infection